Whacked and Rab35 polarize dynein-motor-complex-dependent seamless tube growth. - Schottenfeld-Roames, J.; Ghabrial, A.S. (Nature Cell Biology, 2012)
Seamless tubes form intracellularly without cell-cell or autocellular junctions. Such tubes have been described across phyla, but remain mysterious despite their simple architecture. In Drosophila, seamless tubes are found within tracheal terminal cells, which have dozens of branched protrusions extending hundreds of micrometres. We find that mutations in multiple components of the dynein motor complex block seamless tube growth, raising the possibility that the lumenal membrane forms through minus-end-directed transport of apical membrane components along microtubules. Growth of seamless tubes is polarized along the proximodistal axis by Rab35 and its apical membrane-localized GAP, Whacked. Strikingly, loss of whacked (or constitutive activation of Rab35) leads to tube overgrowth at terminal cell branch tips, whereas overexpression of Whacked (or dominant-negative Rab35) causes formation of ectopic tubes surrounding the terminal cell nucleus. Thus, vesicle trafficking has key roles in making and shaping seamless tubes.